2015
DOI: 10.1590/2359-3997000000074
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative calcium levels as a diagnostic measure for hypoparathyroidism after total thyroidectomy

Abstract: Objective: The aim of the present study was to identify a fast, efficient and low-cost method to diagnose hypoparathyroidism after total thyroidectomy. Materials and methods: One hundred and forty medical records, which contained patients' clinical and laboratory data, were retrospectively analyzed. Patient parathyroid hormone values, which were obtained immediately following operation, were compared with their ionized calcium levels the morning after surgery. This comparison was used to examine the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
2
13
0
5
Order By: Relevance
“…The present study showed highest incidence (30%) in > 50 years of age which is similar to the study conducted by Rosa KM et al 7 This might be due to difference in presentation of benign goitre, papillary and follicular carcinoma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study showed highest incidence (30%) in > 50 years of age which is similar to the study conducted by Rosa KM et al 7 This might be due to difference in presentation of benign goitre, papillary and follicular carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…This was comparable to previous study. 7 Permanent hypoparathyroidism was a less frequent complication, with the incidence of 1.5 to 1.8%. 4,5 Permanent hypocalcaemia was absent in this study during the follow up period of one year.…”
Section: Discussionmentioning
confidence: 99%
“…Another nonexistent important clinical factor was the postoperative calcium level whenever TT was performed. Patients may develop parathyroid glands stunning after TT even with surgery for benign pathology and hence they require calcium taper regimen over 3 weeks [26]. The unavailability of this information made it impossible for the research team to identify the true incidence of postoperative hypocalcemia after TT either temporary or permanent.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of serum calcium in the morning after the surgery is considered a fast and low-cost method to assess parathyroid function in the early post-operative period. 2 The aim of this study was to determine timing of hypocalcemia postoperatively and determine the safest day to discharge post-total/near-total thyroidectomy patients based on serum calcium level.…”
Section: Introductionmentioning
confidence: 99%